2018
DOI: 10.7554/elife.26039
|View full text |Cite
|
Sign up to set email alerts
|

SOXF factors regulate murine satellite cell self-renewal and function through inhibition of β-catenin activity

Abstract: Muscle satellite cells are the primary source of stem cells for postnatal skeletal muscle growth and regeneration. Understanding genetic control of satellite cell formation, maintenance, and acquisition of their stem cell properties is on-going, and we have identified SOXF (SOX7, SOX17, SOX18) transcriptional factors as being induced during satellite cell specification. We demonstrate that SOXF factors regulate satellite cell quiescence, self-renewal and differentiation. Moreover, ablation of Sox17 in the musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 78 publications
(111 reference statements)
0
14
0
2
Order By: Relevance
“…PAX3 protein expression was detected in GFP + MuSCs from both isolated biceps myofibers and plated PAX7 + GFP + MuSCs from control (Pax3 Ctrl) mice (Figures 2D and 2E). We did not observe any PAX3 expression elsewhere in skeletal muscle (Alonso-Martin et al, 2018). This specific PAX3 expression was lost in GFP-traced cells from Pax7 creERT2/+ : Pax3 GFP/flox (Pax3 cKO) mice (Figures 2D and 2E).…”
Section: Differential Loss Of Muscs Exposed To Tcdd Correlates With Muscle-specific Expression Of Pax3mentioning
confidence: 76%
“…PAX3 protein expression was detected in GFP + MuSCs from both isolated biceps myofibers and plated PAX7 + GFP + MuSCs from control (Pax3 Ctrl) mice (Figures 2D and 2E). We did not observe any PAX3 expression elsewhere in skeletal muscle (Alonso-Martin et al, 2018). This specific PAX3 expression was lost in GFP-traced cells from Pax7 creERT2/+ : Pax3 GFP/flox (Pax3 cKO) mice (Figures 2D and 2E).…”
Section: Differential Loss Of Muscs Exposed To Tcdd Correlates With Muscle-specific Expression Of Pax3mentioning
confidence: 76%
“…It is possible that the different expression patterns of Sox genes in tongue muscles could be correlated with the onset of these stages, although the molecular mechanisms regulating the initiation of each phase during tongue development remain unclear. It has been shown that Sox7, 15, 17 and 18 are involved in the function of satellite cells after birth, although these are not exerted at embryonic stages [ 11 13 ]. Therefore, a punctate expression pattern of Sox7, 17, and 18 observed in the embryonic tongue are likely to represent vascularization of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Sox9 in chondrocytes ( Topol et al., 2009 ), Sox17 overexpression was found to increase beta-catenin phosphorylation in adult WM, reducing unphosphorylated, stabilized beta-catenin. In other systems, Sox17 also regulates muscle satellite cell expansion and renewal by inhibiting beta-catenin activity ( Alonso-Martin et al., 2018 ). Strikingly, both beta-catenin and ABC in Olig2 cells were suppressed by SAG in Sox17CKO ( Figures 7 F and 7G), indicating that Sox17-expressing oligodendroglia rely on Smoothened to regulate beta-catenin abundance and activity through the same pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Sox9 in chondrocytes (Topol et al, 2009), Sox17 overexpression was found to increase beta-catenin phosphorylation in adult WM, reducing unphosphorylated, stabilized beta-catenin. In other systems, Sox17 also regulates muscle satellite cell expansion and renewal by inhibiting beta-catenin activity (Alonso-Martin et al, 2018 through the same pathway. The finding that total ABC-expressing cells were not suppressed by SAG in Sox17deficient lesions reveals a cell-specific, Sox17-dependent component of ABC control.…”
Section: Discussionmentioning
confidence: 99%